ASSESSMENT OF THE CAPACITY OF CHANGE OF CAMPECHE LIVESTOCK SYSTEMS TOWARDS AN ORGANIC PRODUCTION MODEL - Victor Daniel Cuervo-Osorio; Bernardino Candelaria Martínez; Elvira María Quetz-Aguirre; Edwin Pérez Sánchez; Sol de Mayo Araucana Mejenes Lopez (Tropical and Subtropical Agroecosystems, 2020)
Background. In Campeche, Mexico, livestock takes place in generally unfertilized grasslands and acahuales, where cattle rarely receive veterinary treatment. These characteristics suggest that some livestock producers could adopt organic production, but their availability for adoption is uncertain and there is little information to assess their feasibility. Objective. Evaluate the change capacity of the conventional livestock systems of Campeche with respect to the organic production model and specify the critical points in management that must be improved in the transition to organic farming. Methodology. Semi-structured interviews were conducted with 74 livestock producers belonging to the BioPaSOS-CATIE Campeche project, in locations in the municipalities of Escárcega, Champotón and Calakmul, as well as direct observations in cattle ranches. The information obtained was used in the Multi-criteria Organic Livestock Conversion Index (OLCI); built with 10 indicators and 35 variables. Results. OLCI showed a low level, but close to the intermediate level of organic standards. Indicators close to standards were: breeds and reproductive management, soil fertilization and feed management. Indicators that move away were: herd safety, ecological weed control in pastures and crops, pest and disease control in pastures and crops, veterinary prevention and treatment, animal welfare, sustainable pasture management and ecological management. Implications. The results obtained are useful for livestock producers in the state of Campeche, since strategies can be generated that allow the conversion of their production systems to an organic livestock model. They are also a benchmark for future research related to the subject of sustainability assessment or organic livestock using indicators. Conclusions. The evaluated livestock systems presented a low level of conversion to the organic production model. Critical points in management that hinder the transition to organic livestock are: sanitary hygiene control, application of synthetic herbicides and insecticides, breastfeeding up to eight months, appropriate stocking rate, use of a silvopastoral system and mainly advisory and training for organic certification, organic development plan and certification, internal control of the organic process and incentives for organic livestock production.